Effects of interleukin 6 and tumor necrosis factor-α on the proliferation of porcine theca interna cells: Possible role of these cytokines in the pathogenesis of polycystic ovary syndrome - Ling Hong; Yunxiang Zhang; Qinghua Wang; Yibing Han; Xiaoming Teng (Elsevier, 2016)
Objective: We studied the effects of interleukin 6 (IL-6) and tumor necrosis factor-α (TNF-α) on the proliferation of porcine theca interna (TI) cells and further elucidated the roles of IL-6 and TNF-α in the pathogenesis of polycystic ovary syndrome. Materials and Methods: TI cells were treated with 10 pg/mL, 100 pg/mL, and 1000 pg/mL IL-6 or TNF-α. TI cell proliferation was then examined by carboxyfluorescein diacetate succinimidyl ester labeling and flow cytometry. Results: Cell proliferation was not significantly different in TI cells cultured in medium alone (control) or in the presence of IL-6. At 72 hours of treatment, the mean fluorescence intensity was significantly lower in TI cells treated with 100 pg/mL and 1000 pg/mL TNF-α than in the control (p < 0.05). Conclusion: TNF-α, but not IL-6, was able to promote TI cell proliferation. Our results suggest that TNF-α might play a role in hyperandrogenism, cortex thickness, and the increased ovary volume observed in polycystic ovaries.